Comparison of high-throughput plant phenotyping (HTPP) approaches to measure radiation use efficiency, a critical trait for improving yields in future - CGIAR Research Program on Wheat (2021)
The models have major implications for breeding; improving C fixation through RUE drives increased yields. Remote sensing models cannot replace ground truth data, but can considerably reduce the amount of time and resources spent, especially on big trials where hundreds of lines could be screened in a matter of hours.